2018
DOI: 10.1002/cncr.31733
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and cancer self‐management behaviors: A scoping review

Abstract: Background Increasing demands on health care systems require patients to take on more active roles in their health. Effective self‐management has been linked to improved health outcomes, and evidence shows that effective self‐management is linked to health literacy (HL). HL is an important predictor of successful self‐management in other chronic diseases but has had minimal testing in cancer. Methods A scoping review was conducted to examine and summarize what is known about the association between HL and self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 46 publications
(253 reference statements)
3
79
0
4
Order By: Relevance
“…For decades, the treatment options for cancer have been expanding, and patients receive cancer treatment during a prolonged period for curative and palliative purposes (1). The treatment is mainly offered on an outpatient basis which requires patients and their caregivers to selfmanage symptoms and side effects from the cancer treatment when staying at home between treatments (2,3). Additionally, patients and their caregivers are expected to report side effects from cancer treatment to their healthcare professionals (HCPs) in order to prevent life-threatening side effects (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…For decades, the treatment options for cancer have been expanding, and patients receive cancer treatment during a prolonged period for curative and palliative purposes (1). The treatment is mainly offered on an outpatient basis which requires patients and their caregivers to selfmanage symptoms and side effects from the cancer treatment when staying at home between treatments (2,3). Additionally, patients and their caregivers are expected to report side effects from cancer treatment to their healthcare professionals (HCPs) in order to prevent life-threatening side effects (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the callers in our study demonstrated the ability to understand and use healthcare information to make appropriate decisions – a degree of health literacy that is presented as an important predictor of successful self-management and autonomous actions. 1 However, the ability to take responsibility as an ‘independent decision-maker’ 27 may be limited regardless of being patient or caregiver due to the association between patients’ symptoms and caregiver burden. 4,16,18,19 Interfering each other in their interdependent relationship may thus be a restraint in the caregiving process that needs acknowledgement from HCPs.…”
Section: Discussionmentioning
confidence: 99%
“…Given the trend towards shorter hospital stays and the increase in outpatient care, patients are increasingly left to self-manage their illness. 1,2 For cancer patients, this may involve handling serious symptoms of the disease and side effects from the treatment given when they are at home between their outpatient treatments. In order to prevent life-threatening side effects, patients are expected to perform self-assessment and report side effects from cancer treatment to their healthcare providers (HCPs).…”
Section: Introductionmentioning
confidence: 99%
“…Bei den aktuell tiefgreifenden Auswirkungen der COVID-19-Pandemie auf das gesellschaftliche, wirtschaftliche und soziale Leben stellt insbesondere die kritische Gesundheitskompetenz, also die Fähigkeit, Gesundheitsinformationen abzuwägen und in den eigenen Kontext zu überführen, eine wichtige Ressource dar [23,24]. Bereits ohne Pandemie ist Gesundheitskompetenz in der Gesellschaft ungleich verteilt, so verfügen sozioökonomisch benachteiligte Bevölkerungsgruppen häufig über eine geringere Gesundheitskompetenz [25][26][27][28]. In der Pandemie verschärfen sich die Lebensbedingungen noch einmal, so sind benachteiligte Bevölkerungsgruppen überproportional von der Pandemie und den pandemiebedingten Einschränkungen betroffen.…”
Section: Hintergrundunclassified